Enhancement of Catalytic Activity and Selectivity for the Gaseous Electroreduction of CO2 to CO: Guidelines for the Selection of Carbon Supports (Adv. Sustainable Syst. 12/2021). (10th December 2021) - Lim, Chulwan; Lee, Woong Hee; Won, Jong Ho; Ko, Young‐Jin; Kim, Sangkuk; Min, Byoung Koun; Lee, Kwan‐Young; Jung, Won Suk; Oh, Hyung‐Suk
Abstract : CO2 Reduction Recently, as a way to address global warming, research on electrochemical carbon dioxide conversion to valuable chemicals has been being actively conducted. In article number 2100216, Won Suk Jung, Hyung‐Suk Oh and co‐workers report the development of silver nanoparticles supported on a carbon nano‐cage as a catalyst for converting CO2 to CO. The catalyst demonstrates high catalytic activity and durability, and is easy to mass‐produce by applying it to a stacked zero‐gap electrolyzer.